Biosynthesis of porphyrins and heme from gamma, delta-dioxovalerate by intact hepatocytes. - Morton, K A (1981)
The purpose of this study was to assess the ability of hepatocytes to synthesize porphyrins and heme from delta-aminolevulinic acid derived from gamma, delta-dioxovalerate and alanine. An alternate pathway for delta-aminolevulinic acid synthesis, in contrast to the condensation of succinate and glycine by delta-aminolevulinate synthase [succinyl-CoA:glycine C-succinyltransferase (decarboxylating), EC 2.3.1.37] has been suggested. This has been supported by the isolation of gamma, delta-dioxovalerate transaminase from liver mitochondria (Varticovski, L., Kushner, J. P. & Burnham, B. F. (1980) J. Biol. Chem. 255, 3742-3747). Gamma, delta-dioxovalerate transaminase catalyzes the formation of delta-aminolevulinic acid by a transamination reaction involving gamma, delta-dioxovalerate and alanine. To assess the significance of this alternate route, we prepared suspensions of respiring rat hepatocytes, which were incubated with optimal concentrations of various additives and then analyzed spectrophotometrically for synthesized porphyrins. No porphyrin synthesis was detected in cell suspensions incubated with succinate(1 mM) and glycine (20 mM). Cell suspensions incubated with gamma, delta-dioxovalerate (0.5-1.0 mM) and alanine (20 mM) synthesized 0.19 nmol of porphyrin per 10(7) cells per 2 hr (SD, 0.057). Cell suspensions incubated with delta-aminolevulinic acid (0.1 mM) synthesized 1.26 nmol of porphyrin per 10(7) cells per 2 hr (range, 1.18-1.32). Incubations with chemically synthesized gamma, delta-dioxo[5-14C]valerate were followed by extraction and purification of porphyrin esters and heme. Liquid scintillation counting revealed radiolabel incorporation into both porphyrins and heme. These studies demonstrate significant tetrapyrrole synthesis by the gamma, delta-dioxovalerate transaminase reaction. That gamma, delta-dioxovalerate is an important precursor of heme in vivo must be considered.